The properties of Sweet Sorghum Syrup Produced by Combined Vacuum Falling Film and Rotary Evaporation - Sudarminto S. Yuwono; Nur Istianah; Dego Y. Ali; Rizkhia J.A. Aghata (Universitas PGRI Semarang, 2020)
The combination of Vacuum Falling Film Evaporator(FFE) and Rotary Evaporator (RE) was conducted in producing sweet sorghum syrup. The aim of this research was to evaluate the performance of single FFE and combined FFE-RE on sorghum syrup concentration. Single FFE was studied at the temperature of 70, 80, and 90°C. The best single FFE treatment was continued by RE at 60, 70, and 80°C. Sweet sorghum that were concentrated using single FFE(90°C) and combined FFE(90°C)-RE(80°C) had the highest Total Soluble Solid(TSS) of 44.2°Brix and 87.53°Brix, also the acceptable lightness(L*) of 30.13 and 25.83 respectively. That combined FFE-RE produced sorghum syrup had the highest overall Hedonic score 3.34 within the taste parameter value of 2.89; color of 3,75; aroma of 3,29; and texture of 3.42. It was also accomplished with the redness(a*) of -2.11, yellowness(b*) of 5.13, turbidity of 387.66 NTU, viscosity of 2036.67cP, and reducing sugar of 52.54%.